Mali : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waivers and Modifications of Performance Criteria; Staff Report; Press Release; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Second Review under the three-year arrangement under the Poverty Reduction and Growth Facility (PRGF) for Mali. Performance under the PRGF-supported program has been generally satisfactory, but there have been delays in implementing structural reforms. Performance criterion on nonconcessional debt was breached in April 2009 when the authorities used loan financing instead of the envisaged bond financing for the programmed reduction in value-added tax (VAT) credit arrears. Authorities have taken corrective measures to restore the track record of structural reforms and address the nonconcessional borrowing.